Kajian Hukum Perjanjian Kerjasama Event Organizer dengan Pengelola Klub Malam dalam Perspektif KUHPerdata - Al Fayyadh, Yasser (Universitas Muhammadiyah Bima, 2025)
Cooperation agreements between event organizers and nightclub venues are contractual relationships used in nightlife events, often leading to legal issues regarding rights, obligations, and risk allocation. This study analyzes such agreements under the Indonesian Civil Code, evidencing their legal validity if they comply with contract requirements. It identifies weaknesses in contractual clauses related to liability, force majeure, and dispute resolution. Recommendations include creating clear, balanced agreements based on good faith and establishing standardized contracts to enhance legal certainty and protection for both parties.